(untitled) - Larsson, Mats (New York, 2004)
There are limits to business development and economic growth. With the help of modern production and information technologies, companies are coming ever closer to the limits of what can be achieved but ultimately nothing can be done in less than no time and at less than no cost. We now need to find areas of competitive advantage that have not yet been fully exploited. This book presents both the problems and the solutions in an accessible way for experts and non-experts alike.
Keywords: Information technology,Technological innovations,Competition,Business enterprises,Economic development; Economic aspects,Economic aspects